2022
DOI: 10.1002/bse.3272
|View full text |Cite
|
Sign up to set email alerts
|

Corporate climate reporting of European banks: Are these institutions compliant with climate issues?

Abstract: This article focuses on climate disclosures from STOXX Europe 600 banks during the 2017–2020 period, comprising 152 company years. Specifically, we analyze compliance based on general and bank‐specific recommendations of the Task Force on Climate‐related Financial Disclosures. Although our results indicate an overall increase in climate reporting quality over time, we identify major reporting gaps, such as consideration of forward‐looking information (particularly related to scenario analyses). We also stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Although these measures were taken to define the perimeter of the ESG phenomenon, there is currently no precise and binding definition at the European level unless the one proposed by the Italian legal framework on ethical and sustainable finance, represented by the adoption in 2016 of the Article 111 bis of the Italian Banking Law (Testo Unico Bancario: T.U.B.). However, despite extensive attention in the literature, a consensus on standard definitions is lacking, hindering the ability to unequivocally categorize a bank as “sustainable” (Arvidsson & Dumay, 2021; Friedrich et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these measures were taken to define the perimeter of the ESG phenomenon, there is currently no precise and binding definition at the European level unless the one proposed by the Italian legal framework on ethical and sustainable finance, represented by the adoption in 2016 of the Article 111 bis of the Italian Banking Law (Testo Unico Bancario: T.U.B.). However, despite extensive attention in the literature, a consensus on standard definitions is lacking, hindering the ability to unequivocally categorize a bank as “sustainable” (Arvidsson & Dumay, 2021; Friedrich et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite extensive attention in the literature, a consensus on standard definitions is lacking, hindering the ability to unequivocally categorize a bank as "sustainable" (Arvidsson & Dumay, 2021;Friedrich et al, 2022).…”
mentioning
confidence: 99%
“…The current climate change situation indicates that our future generations will have to bear and pay for what we are doing to nature through our use of technology, increasing the utilization of carbon as a result (Hansen et al, 2013; Sovacool et al, 2022). Friedrich et al (2022) indicated rapid increases in climate‐relevant risks and opportunities across the board. Karn et al (2022) proposed that managers should examine the latest facts about long‐term monetary benefits associated with corporate environmental sustainability; they may then be able to control negligence toward accepting corporate environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…The driving force behind these net zero commitments has been the international targets established in agreements such as the Paris Agreement, the European Green Deal, COP26, COP27 and upcoming COP summits. However, literature exploring the feasibility of attaining these targets has highlighted several systemic limitations (Friedrich et al, 2022; Jakučionytė‐Skodienė & Liobikienė, 2022). One key issue raised and even addressed during COP 26 is the lack of standardisation and guidance surrounding GHG reporting and accounting methods at the international, national and sectoral levels.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2021, more than 2200 companies have committed to the SBTi, with an increasing number striving to align their climate targets with global decarbonisation trajectories (SBTi, 2022). However, despite the growing popularity of the initiative within the corporate and public spheres, academic literature questions the feasibility of achieving these company‐level climate targets, highlighting several systemic limitations (Friedrich et al, 2022). These limitations include standards that overlook complex business structures and guidance that necessitates access to highly accurate and sector‐specific activity data (de Paula Diniz et al, 2021; Kaur et al, 2022; Ohndorf & Schmitz, 2002).…”
Section: Introductionmentioning
confidence: 99%